PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN ESKULKUL DI KEDAI ESKULKUL BOCIL, BOGOR - Dianawati, Altatit; Inriyani (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
This study aims to determine the influence of Product Quality, Price, Promotion, and Location have a partial or simultaneous effect on the Purchase Decision of Esckul Bocil. The approach used is quantitative using multiple regression analysis. Based on the results of the analysis, it shows that price and location variables partially have a significant effect on purchasing decisions. Meanwhile, the variables of product quality and promotion partially have a significant effect on the purchase decision of Eskulkul Bocil. Based on Test F with a significance level of 5%, it shows that product quality, price, promotion and location have a simultaneous effect on the purchase decision of Eskulkul Bocil. The coefficient of determination (Adjusted R Square) of 0.406 means that 40.6% of purchasing decisions can be explained by variables of product quality, price, promotion, and location. The remaining 59.4% was explained by other variables that were not included in the research model.